Elite dominance and under-investment in mass education: disparity in the social development of the Indian states, 1960-92 - Sarmistha Pal; Sugata Ghosh (Institute for the Study of Labor (IZA), 2007)
Inter- and intra-state disparities in levels of literacy rates in India are striking, especially for the marginalized groups of women and low caste population. The present paper offers an explanation of this disparate development in terms of elite dominance that discriminates against the minority groups of people and systematically under-invests in mass education. We experiment with various indirect economic and political measures of elite dominance. Results based on the Indian state-level data for the period 1960-92 suggest that higher share of land held by the top 5% of the population (a) lowers spending on education as well as total developmental spending and (b) increases total non-developmental spending. Greater proportion of minority representations (female and low caste members) in the ruling government however fails to have any perceptible impact on development (including education) spending in our sample. This analysis also identifies land reform and poverty alleviation as two important policy instruments to erode the initial disadvantage of the marginalised people.
Keywords: 330; Bildungschancen; Soziale Ungleichheit; Elite; Bildungsinvestition; Allgemeinbildende Schule; Frauenbildung; Unterschicht; Indien